Expression of BSP-GFPtpz Transgene during Osteogenesis and Reparative Dentinogenesis. (January 2020) - Vijaykumar, A.; Dyrkacz, P.; Vidovic-Zdrilic, I.; Maye, P.; Mina, M.
Bone sialoprotein (BSP) is a member of the SIBLING family with essential roles in skeletogenesis. In the developing teeth, although the expression and function of BSP in the formation of acellular cementum and periodontal attachment are well documented, there are uncertainties regarding the expression and function of BSP by odontoblasts and dentin. Reporter mice are valuable animal models for biological research, providing a gene expression readout that can contribute to cellular characterization within the context of a developmental process. In the present study, we examined the expression of a BSP-GFPtpz reporter mouse line during odontoblast differentiation, reparative dentinogenesis, and bone. In the developing teeth, BSP-GFPtpz was expressed at high levels in cementoblasts but not in odontoblasts or dentin. In bones, the transgene was highly expressed in osteoblasts at an early stage of differentiation. Interestingly, despite its lack of expression in odontoblasts and dental pulp during tooth development, the BSP-GFPtpz transgene was detected during in vitro mineralization of primary pulp cultures and during reparative dentinogenesis following pulp exposures. Importantly, under these experimental contexts, the expression of BSP-GFPtpz was still exclusive to DSPP-Cerulean, an odontoblast-specific reporter gene. This suggests that the combinatorial use of BSP-GFPtpz and DSPP-Cerulean can be a valuable experimental tool to distinguish osteogenic from dentinogenic cells, thereby providing an avenue to investigate mechanisms that distinctly regulate the lineage progression of progenitors into odontoblasts versus osteoblasts.